Distinctive communication networks in inactive states of β2‐adrenergic receptor: Mutual information and entropy transfer analysis. Issue 11 (11th July 2020) - Sogunmez, Nuray; Akten, Ebru Demet
Abstract: Mutual information and entropy transfer analysis employed on two inactive states of human beta‐2 adrenergic receptor (β2 ‐AR) unraveled distinct communication pathways. Previously, a so‐called "highly" inactive state of the receptor was observed during 1.5 microsecond long molecular dynamics simulation where the largest intracellular loop (ICL3) was swiftly packed onto the G‐protein binding cavity, becoming entirely inaccessible. Mutual information quantifying the degree of correspondence between backbone‐C α fluctuations was mostly shared between intra‐ and extra‐cellular loop regions in the original inactive state, but shifted to entirely different regions in this latest inactive state. Interestingly, the largest amount of mutual information was always shared among the mobile regions. Irrespective of the conformational state, polar residues always contributed more to mutual information than hydrophobic residues, and also the number of polar‐polar residue pairs shared the highest degree of mutual information compared to those incorporating hydrophobic residues. Entropy transfer, quantifying the correspondence between backbone‐C α fluctuations at different timesteps, revealed a distinctive pathway directed from the extracellular site toward intracellular portions in this recently exposed inactive state for which the direction of information flow was the reverse of that observed in the original inactive state where the mobile ICL3 and its intracellular surroundings drove the future fluctuations of extracellular regions.